EXPORTACIÓN DE FÁRMACOS ECUATORIANOS PARA LA INDUSTRIA AVÍCOLA DE EL SALVADOR - Andrade Burbano, Guillermo (2014)
Within the work shows an analysis of opportunities in the market of El Salvador for the marketing of drugs produced in the Ecuador, since the Central American country poultry raising is the engine of the economy, dynamic source to open new jobs. Research is born to know the markets resulting for Ecuador productive and thus offer different goods according to the demand in the area. Before making any investment for the start of negotiations, recommended the study of the internal and external context upon which develops the industry, where the most relevant aspects that help a company investor decisions are considered. The research method used was descriptive - explanatory. According to sources of secondary information, it was found that the pharmaceutical industry for the poultry industry in El Salvador, has been decreasing, i.e. There is no offer for the sector, is from here where you see the need to exploit this market.